Diffusion Processes in Advanced Technological Materials - Gupta, Devendra (Springer Berlin Heidelberg : Imprint: Springer, 2005)
My 12-year-old granddaughter Nina Alesi once asked me, "Grandpa, you are a scientist at IBM, so what do you do?" I tried to reply, "Oh, I watch atoms move. . . " But before I could finish this sentence, my 7-year-old grandson Vinnie interjected, "Grandpa, do atoms play soccer?" This book is about the games atoms play in diffusion and various other properties of materials. While diffusion has been studied for more than 100 years in solids, its importance, excitement, and intellectual chal lenges remain undiminished with time. It is central to understanding the relationship between the structure and properties of naturally occurring and synthetic materials, which is at the root of current technological development and innovations. The diversity of material has led to spec tacular progress in functional inorganics, polymers, granular materials, photonics, complex oxides, metallic glasses, quasi-crystals, and strongly correlated electronic materials. The integrity of complex materials pack ages is determined by diffusion, a highly interactive and synergic phe nomenon that interrelates to the microstructure, the microchemistry, and the superimposed physical fields. While the various physico-chemical properties of the materials are affected by diffusion, they determine diffu sion itself. This book, which is intended to document the diffusive processes operative in advanced technological materials, has been written by pio neers in industry and academia.